(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2023)
In Ethiopia’s mid and lowlands, where rainfall is erratic, finger millet (Eleusine coracana L.) is an important cereal crop. Finger millet yield is low partly due to variety instability and low yield potential. Field experiments were conducted in Boricha, Dore Bafano and Halaba districts of Southern region, Ethiopia, in 2018 and 2019, during the main cropping season from early May to October, to identify finger millet genotypes with high yield and wide adaptation. Eleven finger millet genotypes (ten improved and one local check) were grown in a randomized complete block design with four replications. AMMI analysis generated four principal components (PCs) with PC1 and PC2 being statistically significant (p<0.01). PC1, PC2, PC3, and PC4 contributed 49.85, 32.78, 9.27, and 7.22% of the variation in the GE interaction, respectively. E1 (Boricha2018), E2 (Boricha2019), E3 (Dore Bafano2018), E4 (Dore Bafano2019), E5 (Halaba2018), and E6 (Halaba2019) had a mean yield of 2.77, 3.47, 4.39, 4.26, 3.73, and 3.03 tons ha-1, respectively. Mean yield ranged from 3.03 (genotype Bareda) to 4.42 tons ha-1 (Kako-01). AMMI stability value ranged from 0.23 (genotype Bako-09) to 1.55 (Boneya), and yield stability index ranged from 3 (genotype Bako-09) to 19 (Bareda). AMMI1 and AMMI2 biplots explained 87.28% and 82.63% of the treatment sum of squares, respectively. In the present study, because of its high yield (4.27 tons ha-1) and stability across test environments, genotype Bako-09 would be recommended for widespread cultivation. Int. J. Agril. Res. Innov. Tech. 13(1): 60-66, June 2023